Uso de oligonucleotídeos antisense como estratégia de redução da replicação viral do HIV-1 em cultivo celular - Bastos, Michelle Carolina Dos Santos [UNIFESP] (2019)
INTRODUCTION: HIV-1 infections are a global problem still far from being solved. Although antiretroviral treatment is effective and quite tolerated, it is not able to eradicate the virus from patients. A possible treatment for HIV-1 infection is the use of a specific sequence of antisense oligonucleotides to inhibit the viral replication. OBJECTIVE: Antisense oligos were designed and evaluated for their antiviral activity and cytotoxicity. Antisense oligos anti-HIV-1 GAG 1, GAG 2, GAG 3, GAG 4, LTR 1, LTR 2 were tested for their antiviral activity in primary cells in cultures, combined with the nanoparticles NP-Albumin Albumin Human Sigma A9731- 1G, Albumin Bioscience Catalog # 1001 and Phyto-Hase Enzyme. METHODOLOGY: PBMC cells were acquired by the Ficoll method, resuspended in RPMI supplemented and activated with PHA and IL-2. Trypan Blue viability was performed and the cells were frozen for the standardizations, which were divided into 2 steps. In the first step we standardize the type of the nanoparticle, the concentration of the oligo, use of fresh cells, culture time in front of an infection and its manipulation. In the second stage, 6 oligos with 0.2 μM concentration were tested with the chosen nano (nano 1) in 22 days of culture, with positive and negative controls. The 2mL removed from each condition of the 5 collected samples were centrifuged, the pellet was frozen, and the supernatant was used to quantify viral load. RESULTS: The viability of the cells in the presence of nanoparticles is better in relation to the negative control (without infection and without nanoparticles) and the viability of the cells with the nanoparticle 1 is better than the other nanoparticles. Cell viability is better when oligo is combined with nano 1 compared to other nanoparticles and also when compared to oligo alone. The antisense oligos GAG 2 and GAG 3 had a greater effect against the infection, in the other words, they induced a greater reduction of the viral load in the treated samples when compared with the controls without oligos. CONCLUSION: the cellular viability was better preserved when the nanoparticle 1 was combined with the oligos. With low concentration and low toxicity, the GAG 2 and GAG 3 oligos were the best inhibitors of viral replication during the culture time.